Influenza vaccine effectiveness against laboratory-confirmed influenza in a vaccine-mismatched influenza B-dominant season. Issue 52 (14th December 2020) - Drori, Y.; Pando, R.; Sefty, H.; Rosenberg, A.; Mendelson, E.; Keinan-Boker, L.; Shohat, T.; Mandelboim, M.; Glatman-Freedman, A.; ,
Abstract: Background: The 2017–2018 influenza season in Israel was characterized by the predominance of influenza B Yamagata, with a lesser circulation of influenza A(H1N1)pdm09 and influenza A(H3N2). We estimated vaccine effectiveness (VE) of the inactivated influenza vaccine which was selected for use that season. Methods: End-of-season VE and 95% confidence intervals (CI) against laboratory-confirmed influenza-like illness (ILI) were estimated by means of the test-negative design. Age-specific VE analysis was carried out using a moving age interval. Results: Specimen were obtained from 1, 453 community ILI patients; 610 (42.0%) were influenza-positive, among which 69.7% were B, 17.2% A(H1N1)pdm09 and 13.4% A(H3N2). A 98.6% of molecularly characterized influenza B belonged to the Yamagata lineage. Of the sampled individuals, 1320 were suitable for VE analysis. Of those vaccinated, 90.6% received the inactivated trivalent influenza vaccine (TIV) containing a Victoria lineage influenza B-like virus. VE against influenza A differed by age, with the highest VE of 72.9% (95%CI 31.9–89.2%) observed in children 0.5–14 years old, while all ages VE was 46.6% (95%CI 10.4–68.2%). All ages VE against influenza B was 23.2% (95%CI −10.1–46.4%) with age-specific analysis showing non-significant VE estimates. Utilizing a moving age interval of 15 years, afforded a detailed age-specific insight into influenza VE against the influenza viruses circulating during the 2017–2018 season. Conclusions: The moderate-high 2017–2018 influenza A VE among children and adolescents, supports seasonal influenza vaccination at a young age. The low VE against influenza B in Israel, is most likely the result of influenza B/TIV-mismatch.